Dreaming and parasomnias – A case with severe parasomnia overlap and its treatment - Tuisku Katinka; Sandman Nils; Partinen Markku; Paunio Tiina (Psykiatrian Tutkimussäätiö, 2025)
Dreams are experiences during sleep that are internally generated by the brain. Dreaming is a common phenomenon during normal sleep and dreaming may occur in all sleep stages. Brain is active during sleep, but the perceptual connection to environment is mostly turned off.  During dreaming, the contents of dreams can, however, be affected by both external and internal stimuli. Dream recall is associated with higher frequency brain activity during sleep, typical of REM-sleep and arousals.
During parasomnias, dream experiences may be disturbed, behaviorally manifested or mixed with waking reality. Parasomnias are sleep disorders characterized by incomplete transitions between sleep and wake. Abnormal motor, sensory, or behavioral manifestations of parasomnias occur at sleep onset, within sleep, or during arousal from sleep. Various sensory stimuli are able to disturb sleep causing arousals or partial awakenings typical of parasomnias.
Differential diagnosis of parasomnias include patient report of recalled and enacted dream content, timing and onset-age of parasomnia episodes, witnessed sleep behavior, and polysomnographic findings about the sleep stage and the mechanism of episodes. In adults, parasomnias may have significant negative effects on wellbeing and even violent consequences. A patient case with severe parasomnia overlap disorder and its treatment is presented.